Challenges during bilateral total temporomandibular joint replacement for ankylosis in ankylosing spondylitis patient-a case report - Devalina Goswami; Apoorva Singh; Poonam Yadav; Ajoy Roychoudhury (Elsevier, 2021)
Alloplastic replacement of temporomandibular joint is the preferred treatment for temporomandibular joint ankylosis (TMJA) in ankylosing spondylitis (AS) patients. These patients exhibit neck rigidity due to fixed flexion deformity or fusion of vertebrae that make the intubation and surgical positioning of patients difficult and challenging. Chin on the chest makes tracheostomy almost impossible. Fiberoptic-assisted intubation is recommended. It is mandatory that no neck flexion or rotation is performed during intubation or surgical positioning. The use of an operating table that permits lateral tilt is recommended for surgical positioning. 15-20-degrees tilt of table or a lateral positioning of the patient, can provide sufficient neck support and reduce the chances of lateral neck rotation or neck flexion. Improper positioning may result in readjusting the patient's neck repeatedly during operative procedure. This may cause serious neurological injury. Minimal documentation exists for proper and secure positioning of the patient for bilateral alloplastic joint replacement in AS patients. The authors present a case of bilateral TMJA in AS patient who was managed successfully by awake fiberoptic intubation and lateral positioning for alloplastic total joint replacement (TJR).